Pharmacokinetic and pharmacodynamic modelling of marbofloxacin administered alone and in combination with tolfenamic acid in calves - Sidhu, Pritam K. (2010)
In a four-period, cross-over study, the fluoroquinolone antibacterial drug marbofloxacin (MB) was administered to calves, alone and in combination with the nonsteroidal anti-inflammatory drug tolfenamic acid (TA). Both drugs were administered intramuscularly (IM) at doses of 2 mg/kg. A tissue cage model of inflammation, based on the actions of the mild irritant carrageenan, was used to evaluate the pharmacokinetics (PK) of MB and MB in combination with TA. MB mean values of area under concentration-time curve (AUC) were 15.1 μg·h/mL for serum, 12.1 μg·h/mL for inflamed tissue cage fluid (exudate) and 9.6 μg·h/mL for noninflamed tissue cage fluid (transudate). Values of C(max) were 1.84, 0.35 and 0.31 μg/mL, respectively, for serum, exudate and transudate. Mean residence time (MRT) of 23.6 h (exudate) and 22.6 h (transudate) also differed significantly from serum MRT (8.6 h). Co-administration of TA did not affect the PK profile of MB. The pharmacodynamics of MB was investigated using a bovine strain of Mannheimia haemolytica. Time-kill curves were established ex vivo on serum, exudate and transudate samples. Modelling the ex vivo serum time-kill data to the sigmoid E(max) equation provided AUC(24 h) /MIC values required for bacteriostatic (18.3 h) and bactericidal actions (92 h) of MB and for virtual eradication of the organism was 139 h. Corresponding values for MB + TA were 20.1, 69 and 106 h. These data were used to predict once daily dosage schedules for a bactericidal action, assuming a MIC(90) value of 0.24 μg/mL, a dose of 2.6 mg/kg for MB and 2.19 mg/kg for MB + TA were determined, which are similar to the currently recommended dose of 2.0 mg/kg.